2014
DOI: 10.1136/acupmed-2014-010612
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Decreases Matrix Metalloproteinase-2 Activity in Patients with Migraine

Abstract: Objective To evaluate the effect of acupuncture on the serum matrix metalloproteinase-2 (MMP-2) level and activity in patients with migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…Acupuncture treatment could also significantly decrease matrix metalloproteinase-2 (MMP-2) activity in patients with migraine without affecting the MMP-2 concentrations. The analgesic effect of acupuncture might be associated with this decrease [54]. Acupuncture combined with electroacupuncture could decrease plasma glutamate levels, which were found significantly increased in rats during acute migraine attacks, and thereby relieving pain [55].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture treatment could also significantly decrease matrix metalloproteinase-2 (MMP-2) activity in patients with migraine without affecting the MMP-2 concentrations. The analgesic effect of acupuncture might be associated with this decrease [54]. Acupuncture combined with electroacupuncture could decrease plasma glutamate levels, which were found significantly increased in rats during acute migraine attacks, and thereby relieving pain [55].…”
Section: Discussionmentioning
confidence: 99%
“…[11] There are also studies showing the efficacy of acupuncture in reducing the number of migraine attacks. [12,13] Some authors also reported that acupuncture accelerated healing process, resolved edema, and provided analgesia in a case of metatarsal fracture. [14] In conclusion, to the best of our knowledge, this is the first case report to show the effectiveness of acupuncture in the treatment of venous insufficiency and varicose veins.…”
Section: Discussionmentioning
confidence: 99%
“…16 Studies have assessed neurovascular blood flow via Doppler imaging studies 17,18 ; function and structure of the resting brain of migraine patient pre-and postacupuncture using functional magnetic resonance imaging (MRI) 19 ; and neurobiological changes secondary to acupuncture. [20][21][22] These studies seek to further qualify the various physiological effects that acupuncture have on the brain and migraine headache.…”
Section: Neurobiological Mechanisms On Use Of Acupuncturementioning
confidence: 99%
“…In sum, these studies appear to establish reasonable safety and efficacy of acupuncture for treatment of migraines in adults. 21 Additional research targeting various types of acupuncture for both acute and preventive treatments of migraine in adults and children are reviewed later.…”
Section: Neurobiological Mechanisms On Use Of Acupuncturementioning
confidence: 99%